Москвофільство галичини: до історії проблеми - Фаріон, Ірина; Farion, Irina (Видавництво Львівської політехніки, 2018)
Досліджено ментально-політичну проблему москвофільства в Галичині в історичній ретроспективі: від кінця ХVI до початку ХХ століття. Проаналізовано зародження та еволюцію ренегатських ідей москвофільства від обґрунтування українсько-московської релігійно-етнічної єдності у посольстві львівських братчиків 1592 року до абсолютної підтримки Росії під час її окупації Галичини в 1914 році.

Introduction. The article explores sources of mental and political problem of muscophilism in Galicia in the historical retrospective from the end of the XVI to the beginning of the XX century. Purpose. Our purpose is to identify and discover chronologic sources of muscophilism and analyse its transformation through religious and political activity of prominent personalities of Galicia. Methods. Historical and descriptive method is used, with the help of it the background for uprise of muscophilism and its essence as ideology of denationalization and defeatism is revealed. Result. The result of the research determines that muscophilism ideas in Galicia, particularly in Lviv, were initiated by the embassy of Lviv brotherhood members and Lviv metropolitan Dionysius Balaban in 1952, who in their appeal to Moscowian tsar Fyodor of rebuilding the burnt Dormition Church in Lviv actually laid ideological foundation for merging of Ukrainians and Muscovites. Muscophilism already as a political stream, influenced by counterrevolutionary events and «Spring of the Nations» of 1848 failure, reached its culmination in the 50s of the XIX century. Originality. Originality of the research consists in the analysis of primary historical source of muscophilism in Galicia and beginnings of ideological foundations forming of ethnic and religious «unity» of Galicia and Muscovy, that is modern idea of «russkiy mir». Conclusion. Muscophilism is the ideology of denationalization and defeatism that became the outpost of occupation of Galicia by Russia during the First World War of 1914, and finally led to hybrid Russian-Ukrainian war of 2014 under hybrid motto Iedyna kraina [ukr] – iedinaia strana [rus] (United country [eng]). The proposed material has fundamental ideological meaning in the development of independent Ukrainian State. For the purpose of decolonization of thought it should be used in all humanities courses of higher school and be widely promoted thorough various projects in mass media
Muscophilism of galicia: on history of the issue
Keywords: москвофільство; історична ретроспектива; російсько-українська війна; moscowophilism; historical retrospective; Russian-Ukrainian War; 329.4; 94 (477.83/.86)»18/19»